Survey on Reversible Texture Synthesis Techniques - Ramya.K, Ruth; M, Karthik.; Priyanka.M, Yamini; BH, Vinutna (International Journal of Engineering and Technology, 2018)
Encryption is the technique by which we can encode the expected snippet of In Advanced Image Steganography the message is covered up in a picture such that the spectators can't figure that it is not an ordinary picture. These days security is an essential issue while transmitting a message. To start with we have scrambled the message to a picture which needs a secret key to be unscrambled. At that point we have shrouded that picture inside another picture by steganography approach. By this two level concealing we can guarantee more grounded security. We propose a novel approach for steganography using a reversible surface union. A surface union process resample's a more diminutive surface picture, which joins another surface picture with an equivalent close-by appearance and a subjective size. We work the surface union process into steganography to cover puzzle messages. Instead of using a present cover picture to cover messages, our figuring covers the source surface picture and embeds riddle messages through the method of surface mix. This empowers us to isolate the puzzle messages and source surface from a stego designed surface. Our approach offers three specific positive conditions. To begin with, our arrangement offers the embedding’s furthest reaches that is in respect to the measure of the stego surface picture. Second, a steganalytic figuring isn't presumably going to vanquish our steganographic approach. Third, the reversible limit gained from our arrangement gives convenience, which grants recovery of the source surface. Trial comes to fruition have affirmed that our proposed estimation can give distinctive amounts of embedding’s limits, make an apparently possible surface pictures, and recover the source surface.
Keywords: ASCII Integer; Cover Image; FiboSum; Pixel Mapping; Stego-image.